'We fuck and friends don't fuck': BFFs, lesbian desire, and queer narratives. Issue 6 (3rd July 2018) - McBean, Sam
ABSTRACT: The 'BFF' label is often used by mainstream media to closet what are actually lesbian relationships. Responses to the misuses of the label insist that friendship is an anachronistic code that erases same-sex desire in the present. This article considers whether a different approach is possible – whether friendship might not only erase lesbian desire but might enable queer narratives. It takes as its case study MTV's Faking It (2014–2016), a half-hour sitcom in which teenage BFFs, Amy and Karma, are misrecognised as lesbians. Faking It flips the misrecognition of lesbians as BFFs, having BFFs read as a lesbian couple. Faking It is a self-conscious show that understands itself as coming 'after' a degree of mainstreaming when it comes to LGBTQ representation on TV – Amy and Karma are celebrated by their peers and told they do not need to hide behind friendship. Yet, Faking It entwines friendship and queerness in productive ways, suggesting that the narrative of friendship might contain queer narrative possibilities. In dialogue with queer thinking on time and narrative, this article insists on reading the BFF narrative as overlapping with same-sex female desire in ways that are productive of, and enable, queer narrative.